Antiretroviral Agents and Prevention of Malaria in HIV-Infected Ugandan Children - Achan, Jane; Kakuru, Abel; Ikilezi, Gloria; Ruel, Theodore; Clark, Tamara D.; Nsanzabana, Christian; Charlebois, Edwin; Aweeka, Francesca; Dorsey, Grant; Rosenthal, Philip J.; Havlir, Diane; Kamya, Moses R (The New England Journal of Medicine, 2012)
Human immunodeficiency virus (HIV) protease inhibitors show activity against Plasmodium falciparum in vitro. We hypothesized that the incidence of malaria in HIV infected children would be lower among children receiving lopinavir–ritonavir– based antiretroviral therapy (ART) than among those receiving nonnucleosidereverse transcriptase inhibitor (NNRTI)–based ART.
Keywords: Malaria; HIV-Infected; Children